Human leukocyte antigens are associated with salivary level of active MMP‐8 - Matti Mauramo; Elina Mauramo; Timo Sorsa; Taina Tervahartiala; Ismo T. Räisänen; Tuomas Waltimo (Wiley, 2021)
Abstract Objectives This case control study examined the associations of HLA antigens and periodontitis with the salivary level of active MMP‐8 (aMMP‐8). Materials and Methods A total of 202 subjects, registered as Swiss bone marrow donors, participated in the study. HLA‐A, ‐B, and ‐C types were determined by serology or PCR. Saliva samples were collected from subjects, followed by a periodontal examination. The salivary level of aMMP‐8 was determined with immunofluorometric assay. Results The mean salivary level of aMMP‐8 was directly comparable to the grade of periodontitis and increased from healthy to mild/moderate to severe (125.0 ± 132.1, 200.6 ± 170.2, 290.1 ± 202.3 ng/ml; p < 0.001 between each group, respectively). The only association between the HLA types and the salivary level of aMMP‐8 was observed in subjects with HLA‐A11. Subjects with healthy periodontium and HLA‐A11 had a lower level of aMMP‐8 (49.2 ± 32.5 ng/ml) compared with subjects without HLA‐A11 (123.6 ± 119.2; p = 0.048). Among subjects with periodontitis, a higher level of aMMP‐8 (394.2 ± 255.6 ng/ml) was observed in subjects with HLA‐A11 compared with subjects without HLA‐A11 (201.1 ± 146.1 ng/ml; p < 0.002). This finding was statistically significant also after adjusting for sex, age, smoking, tooth brushing and the number of medications (p < 0.05). Conclusions HLA‐A11 is associated with the salivary level of aMMP‐8 which contributes to the subject's immune and inflammatory response in periodontium.